Innovation in the Development of 2D Animation-Based Visualization Learning Media Using the ADDIE Method to Improve Student Learning Outcomes - Lustiyono Prasetyo Nugroho; Rujianto Eko Saputro; Fandy Setyo Utomo (JINoP (Jurnal Inovasi Pembelajaran), 2025)
The development of information technology has not been fully utilized in science learning at vocational high schools, where conventional methods still dominate and make it difficult for students to understand concepts. This study aims to develop information technology and create a new product in the form of 2D visualization. The study employed a development approach based on the ADDIE model and focused on developing learning media for Grade 10 science subjects using animated videos. Three aspects were evaluated: feasibility, practicality, and effectiveness. The assessment of these aspects showed that students were able to improve their learning outcomes and conceptual understanding in science subjects. Based on expert evaluations, media experts provided an average score of 87%, while material experts rated it at 80%. Teacher responses reached 94%, and student responses were 94.49%. The results of the post-test stage indicated an average achievement of 92.25%, with the highest score of 100 and the lowest score of 70. These findings suggest that the use of animated videos can effectively enhance students’ learning outcomes and conceptual understanding. It is recommended that future studies expand the method, scope of materials, and sample size to further address the lower range of student scores.